Change of Values in Lithuania in the Process of European Integration - Liubinienė, Vilmantė (Sociologija. Mintis ir veiksmas, 2002)
In the process of European integration and seeking for the membership inside the European Union, the problem of value change remains very significant if we are to understand processes of change not only in the economy, politics, and society in general, but in the minds, outlooks and social behaviour of the people as well. The purpose of this paper is to identify similarities and differences in attitudes, beliefs and value priorities between the three Baltic countries – Lithuania, Latvia, Estonia and to suggest historical, economic, social, cultural, etc., aspects of these countries that may account for the differences.
Keywords: values; European integration; post-communist society; Lithuania; Latvia; Estonia